After the Tournament: Outcomes and Effort Provision - Andrew McGee; Peter McGee (Institute for the Study of Labor (IZA), 2013)
Modeling the incentive effects of competitions among employees for promotions or financial rewards, economists have largely ignored the effects of competition on effort provision once the competition is finished. In a laboratory experiment, we examine how competition outcomes affect the provision of post-competition effort. We find that subjects who lose arbitrarily decided competitions choose lower subsequent effort levels than subjects who lose competitions decided by their effort choices. We explore the preferences underlying this behavior and show that subjects' reactions are related to their preferences for meritocratic outcomes.
Keywords: C90; J30; D03; 330; tournaments; counterproductive behavior; promotions; experiment